Contaminantes ambientais emergentes e variáveis físicas, químicas e microbiológicas de água de consumo humano - Vargas, Patricia Raquel (2023)
Groundwater is important in maintaining the flow of water, being used in numerous activities from human consumption, irrigation, agricultural and commercial production. The objective of the research was to carry out a macroscopic environmental analysis characterizing the environmental conditions around deep wells, identify and quantify physical, chemical and microbiological variables, as well as active principles of pharmaceuticals and active ingredients of pesticides in water from deep wells (in two different times) of private rural properties in the Rio Grande do Sul, State, under the land uses and occupation of native field soil, irrigated rice, seasonal crop (soybean, corn, wheat), dairy productivity and swine farming, for later compare with current legislation (national and international) potability water. Environmental macroscopic analysis, 60% of the deep wells obtained obtained a degree of preservation in Class C (Reasonable), due to the lack of local protection (without enclosure) in the surroundings, proximity to residences (< 50 m) and low preservation of vegetation are factors that facilitate/potentiate contamination and may interfere with water quality, together with the proximity of these wells to activities carried out on these properties, they may be sources of waste generation capable of contaminating groundwater. For the physical and chemical variables, the total manganese and iron are above the maximum permitted values allowed (MPV) by the Legislation in force in the land uses and occupation with dairy productivity and swine farming; whereas pH, total hardness, fluoride, apparent color, turbidity, total ammonia and nitrite are below the MPV allowed for potable water for human consumption, under different land uses and occupation. Temperature, total alkalinity, total phosphorus, electrical conductivity, nitrite + nitrate, Kjedahl total nitrogen, dissolved oxygen and biochemical oxygen demand are not mentioned in the Drinking Water current Legislation. The microbiological variables, total Coliforms and Escherichia coli were detected in the waters of all deep wells under different land uses and occupation, being in disagreement with the current legislation. Pharmaceuticals and pesticides were detected at both times of water collection and land use and occupation, totaling 8 active ingredients pharmaceuticals and 34 active ingredients pesticides, with the highest frequency of occurrence being caffeine and sulfadoxine (pharmaceuticals), 2,4-D and diuron (pesticides). When compared with the water potability legislation, these are below the MPV allowed, for those contained in these regulations. According to the results obtained, it is concluded that the water for human consumption from the deep wells studied under different land uses and occupation are not suitable for human consumption, requiring some treatment process for this, in addition to passing on rural producers information on necessary/essential corrective actions that must be carried out around these deep wells, in order to increase the groundwater preservation area, making them potable. It is believed that this exchange of scientific information with society will contribute to the reduction of residues of chemical compounds used in agriculture and other rural activities (pesticides and pharmaceuticals) in this water, which is of vital importance for human and environmental health.